The Economic Succession Doctrine in Private Enforcement of EU Competition Law: 'Nothing Extraordinary' After Skanska Industrial? - Marco Botta (Market and Competition Law Review)
The article analyses the recent judgment of the Court of Justice of the European Union (CJEU) in Skanska Industrial. In its preliminary ruling, the CJEU recognised for the first time the so-called “economic succession doctrine” in damage claims concerning a breach of EU competition rules. In the judgment, the CJEU relied on its well-established case law. From this point of view, the ruling is “nothing extraordinary”. Nevertheless, the judgment represents an important milestone that contributes to the development of damage claims in Europe. The article first discusses the origins of the economic succession doctrine, which derives from the broad concept of “undertaking” developed by the CJEU case law and the so-called “single economic entity” doctrine. Afterwards, the article discusses the Skanska Industrial case, in particular by comparing the opinion of Advocate General (AG) Wahl with the CJEU ruling in the case. The article concludes by discussing the potential consequences of the CJEU ruling in Skanska Industrial on private enforcement of EU competition law, as well as the questions that remain open after the judgment. After Skanska Industrial, it remains unclear how the disclosure of evidence will take place in practice in the context of a damage claim following a corporate restructuring. Secondly, the limits of the economic succession doctrine remain unclear: it is unclear when a corporate restructuring indeed leads to the establishment of a “new” undertaking, free from the antitrust liability acquired by its predecessor. Finally, it remains unclear whether Skanska Industrial case law could also be extended to other remedies besides damage claims, such as actions requesting a court injunction, compensation for unjust enrichment, or a declaration that a contract is null and void. The article argues that in the coming years the CJEU will probably be called to clarify Skanska Industrial case law in order to answer these remaining questions.